A Strategic and The Business Development of Bumbu Bu Erna - Salsabilla, Adibah Ardelia; Fakhri, Erie Awalil (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to analyze the branding strategy of Bumbu Bu Erna, an MSME producing ready-to-use cooking spices and herbs in Probolinggo Regency, and to develop strategic recommendations for strengthening brand identity, increasing market acceptance, and supporting business growth. Design/Methodology/Approach – This study employs a quantitative approach to identify key factors influencing business performance and consumer acceptance of Bumbu Bu Erna products. Data were analyzed to evaluate the current branding strategy, market response, and opportunities for product and service development. The analysis focuses on the role of branding in creating product differentiation and delivering added value to consumers. Findings – The findings indicate that implementing effective and innovative branding strategies can enhance consumer brand awareness and preference toward Bumbu Bu Erna products. Furthermore, a comprehensive evaluation of current business conditions provides valuable insights for improving product quality, developing new product variations, and enhancing services to respond to increasing market demands.   Originality/Value This research is original in examining branding strategy within a small-scale culinary MSME context in a regional area. The findings provide practical value by offering insights into how effective branding enhances market acceptance and supports sustainable business development.